Matrix regeneration proteins in the hypoxia-triggered exosomes of shoulder tenocytes and adipose-derived mesenchymal stem cells - Thankam, Finosh G. (Mol Cell Biochem, 2019)
Regenerative functions of exosomes rely on their contents which are influenced by pathological stimuli, including hypoxia, in rotator cuff tendon injuries (RCTI). The hypoxic environment triggers tenocytes and adjacent adipose-derived mesenchymal stem cells (ADMSCs) to release regenerative mediators to the ECM via the exosomes which elicit autocrine/paracrine responses to protect the tendon matrix from injury. We investigated the exosomal protein contents from tenocytes and subcutaneous ADMSCs from the shoulder of Yucatan microswine cultured under hypoxic conditions (2% O(2)). The exosomal proteins were detected using high-resolution mass-spectrometry nano-LC-MS/MS Tribrid system and were compiled using ‘Scaffold’ software. Hypoxic exosomes from tenocytes and ADMSCs carried 199 and 65 proteins, respectively. The key proteins identified by mass spectrometry and associated with ECM homeostasis from hypoxic ADMSCs included MMP2, COL6A, CTSD and TN-C and those from hypoxic tenocytes were THSB1, NSEP1, ITIH4 and TN-C. These findings were confirmed at the mRNA and protein level in the hypoxic ADMSCs and tenocytes. These proteins are involved in multiple signaling pathways of ECM repair/regeneration. This warrants further investigations for their translational significance in the management of RCTI.